2022
DOI: 10.1155/2022/2552990
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology Characteristics and Antibiotic Resistance Associated with Urinary Tract Infections Caused by E. coli

Abstract: Introduction. In individuals with urinary tract infections, Escherichia coli (E. coli) is an ubiquitous causative agent and antibiotic resistance is on the rise throughout the world. Therefore, early diagnosis and appropriate choice of antimicrobials are essential. The purpose of our study is to describe some of the clinical and epidemiological characteristics and the laboratory test results of children treated in our hospital for urinary tract infections caused by E. coli. Methods. The study included 128 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Since high abundance of VAs and PVAs was detected in the urine samples of patient group, we are interested in whether resistant genes are induced in gut microbes. E. coli and S. aureus were chosen as target species because both of them are commensal microbes and representative antibiotic-resistant bacteria in gram-negative bacteria and gram-positive bacteria, respectively [ 32 , 33 ]. In our study, they showed different response to VAs and PVAs exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Since high abundance of VAs and PVAs was detected in the urine samples of patient group, we are interested in whether resistant genes are induced in gut microbes. E. coli and S. aureus were chosen as target species because both of them are commensal microbes and representative antibiotic-resistant bacteria in gram-negative bacteria and gram-positive bacteria, respectively [ 32 , 33 ]. In our study, they showed different response to VAs and PVAs exposure.…”
Section: Discussionmentioning
confidence: 99%